Accuracy and interrater reliability for the diagnosis of Barrett's neoplasia among users of a novel, portable high‐resolution microendoscope. Issue 1 (26th February 2013) - Vila, P. M.; Kingsley, M. J.; Polydorides, A. D.; Protano, M.‐A.; Pierce, M. C.; Sauk, J.; Kim, M. K.; Patel, K.; Godbold, J. H.; Waye, J. D.; Richards‐Kortum, R.; Anandasabapathy, S.
Summary The high‐resolution microendoscope (HRME) is a novel imaging modality that may be useful in the surveillance of Barrett's esophagus in low‐resource or community‐based settings. In order to assess accuracy and interrater reliability of microendoscopists in identifying Barrett's‐associated neoplasia using HRME images, we recruited 20 gastroenterologists with no microendoscopic experience and three expert microendoscopists in a large academic hospital in New York City to interpret HRME images. They prospectively reviewed 40 HRME images from 28 consecutive patients undergoing surveillance for metaplasia and low‐grade dysplasia and/or evaluation for high‐grade dysplasia or cancer. Images were reviewed in a blinded fashion, after a 4‐minute training with 11 representative images. All imaged sites were biopsied and interpreted by an expert pathologist. Sensitivity of all endoscopists for identification of high‐grade dysplasia or cancer was 0.90 (95% confidence interval [CI]: 0.88‐0.92) and specificity was 0.82 (95% CI: 0.79‐0.85). Positive and negative predictive values were 0.72 (95% CI: 0.68‐0.77) and 0.94 (95% CI: 0.92‐0.96), respectively. No significant differences in accuracy were observed between experts and novices (0.90 vs. 0.84). The kappa statistic for all raters was 0.56 (95% CI: 0.54‐0.58), and the difference between groups was not significant (0.64 vs. 0.55). These data suggest that gastroenterologists can diagnose Barrett's‐related neoplasia on HRME images with high sensitivity and specificity, without the aid of prior microendoscopy experience.